Does Product Semantics Matter in Stimulating Impulse Buying Behavior for Internet Products? - Huang, Xiangmeng; Cai, Ruilin (Frontiers in Psychology, 2021)
Design-driven innovation has become the source of the third-dimensional innovation driving force behind technology and outside the market, aiming to explore breakthrough innovation in product semantics for Internet products. This research tries to define the concept of product semantics and construct a consumer purchase decision model for Internet products with product semantic perception as the antecedent variable. In addition, how product semantics could stimulate consumers' expected regret and impulse purchase for Internet products is explained. The research finds that product semantic perception significantly affects consumers' expected inaction regret, which promotes their impulse purchase intention for Internet products; and expected inaction regret partially mediates between product semantic perception and impulse purchase intention. Self-control ability of consumers negatively moderates the relationship between their expected inaction regret and impulsive purchase intention for Internet products. Thus, the “non-use function” design of product semantics can effectively meet and lead the spiritual and cultural needs in hedonistic Internet shopping for consumers.